Disturbance Attenuation of Asymmetric Structure by LMI Based Optimal State Feedback Controller with Saturated Actuators - Sever, Mert; Goktas, Gulay; Yazici, Hakan; Kucukdemiral, Ibrahim Beklan (IEEE, 2015)
This paper is concerned with the design of linear matrix inequalities (LMIs) based optimal state-feedback controller design for seismically excited asymmetric structures (AS) having stiffness irregularities. The system is modelled in terms of mass, natural frequencies, damping ratio and eccentricities to easily obtain torsionally flexible (TF) model. A one storey, two-way asymmetric structural system is used to illustrate the effectiveness of the approach through simulations. The modelled system has bi-lateral and rotational degrees of freedom. Frequency responses show the effectiveness of proposed controller by means of a decrease in the peak values of translation at each resonance frequency. Moreover, the time domain simulation results, acquired by using real time-history data of San Francisco and El Centro Earthquakes also show that proposed controller is very effective in reducing vibration amplitudes of each direction by applicable control signals and guaranteeing the stability of the closed loop system.
Keywords: asymmetric structure; active vibration control; earthquake induced vibration; actuator saturation; linear matrix inequalities; VIBRATION CONTROL; SLIDING-MODE; SYSTEM; BUILDINGS; Engineering